'An Inverted Eden': Modernity and Anti-Modernism in D'Arcy Cresswell's The Forest. Issue 3 (August 2020) - Carlston, Erin G.
Abstract : In 1952, D'Arcy Cresswell published a verse play, The Forest, set in New Zealand's forested Southern Alps. In what Cresswell called a 'tremendous defense of homosexuality', The Forest depicts a pair of gay male poets pitted against the archangel Lucifer and women, who are in league together to force men to work the land and thereby desacralize it. Cresswell argues that the pressures on Pākehā men to be economically productive and heterosexually reproductive are manifestations of a literally Satanic plot to alienate men from one another and Nature. While many of Cresswell's New Zealand literary contemporaries espoused a Pākehā masculinity involving matey comradeship and a life spent working the land, Cresswell celebrates a New Zealand wilderness he perceives as the last refuge of male love and inspired poetry. Simultaneously queering Milton, inverting Judeo-Christian history by relocating Eden in the Antipodes, and reversing New Zealand history by undoing the modernity that settler colonialism had created, Cresswell counters the terms of his own exclusion from the literary canon by imagining a world upside-down – and inside-out.